Magnetic field line separation by random ballistic decorrelation in transverse magnetic turbulence - Yannawa C. (2023)
The statistics of the magnetic field line separation provide insight into how a bundle of field lines spreads out and the dispersion of non-thermal particles in a turbulent environment, which underlies various astrophysical phenomena. Its diffusive character depends on the distance along the field line, the initial separation, and the characteristics of the magnetic turbulence. This work considers the separation of two magnetic field lines in general transverse turbulence in terms of the magnetic power spectrum in three-dimensional wavenumber space. We apply non-perturbative methods using Corrsin's hypothesis and assume random ballistic decorrelation to calculate the ensemble average field line separation for general transverse magnetic turbulence. For 2D + slab power spectra, our analytical formulae and computer simulations give similar results, especially at low slab fraction. Our analytical expression also demonstrates several features of field line separation that are verified by computer simulations.